The Impact of Dividend Policy on Stock Prices: Evidence from Nepalese Banking Sector - Gurung, Jas Bahadur; Chapagain, Ramkrishna; Baral, Amrit; Boro, Lija (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The study examined the impact of dividend policy on market price of share in banking sector of Nepal. Out of 27 commercial banks, 10 banks have been selected under convenience sampling with ten years data for the period 2068/69 to 2077/78 were taken for the analysis. Panel data regression models (random effect model) has been utilized to analyze the data as the Hausman test suggest the random effect model is the most appropriate for describing the relationship among the given variables. The result indicates that earning per share, dividend per share, price-earnings ratio and retained earnings have a positive relationship on stock prices of commercial banks. The study concluded that dividend payments lead to a rise in the market price of a stock. Hence, it can be inferred from the outcome of the random effect regression model that it is consistent with the applicable methods related to dividend policy, indicating that there is a noteworthy impact of dividend policy on the stock price of companies. The findings of this study will contribute to the existing literature on dividend policy and market price of share, especially in the context of Nepal. The study will also provide important implications for investors, policymakers, and companies in making decisions regarding dividend rules and its impact on the stock prices.